Different profiles of well-being status in osteoarthritis conditions, type II diabetes mellitus, and hypertension based on gender - Syamsul Ari Wicaksono; Farid Rahman (Physical Therapy Journal of Indonesia, 2023)
Background: Degenerative diseases are becoming more prevalent in developing nations, including gender. This impacted well-being, the need to improve personal well-being in health, movement, religion, work, diet, emotional well-being, family, and friends. Methods: Sectional research design used analytical observation. One hundred twenty-one participants made up the sample by the researcher's inclusion criteria. Assessment wheel for the Instrument Model for Healthy Living. They analyzed data with both single and multiple variables. Results: A p-value of 0.907 was found for the relationship between health status and conditions such as osteoarthritis, type II diabetes, and hypertension. A p-value of 0.623 was observed for gender-based well-being status. Osteoarthritis, type II diabetes, and hypertension received a p-value of 0.904 for the gender interaction on group health. Conclusion: The groups with osteoarthritis, type II diabetes mellitus, and hypertension all had similar levels of well-being. Gender has no bearing on one's level of well-being. In the groups with type II diabetes, hypertension, and osteoarthritis, there were no gender differences in the well-being interactions.